Calculations and Experimental Studies of TAGzT under High Pressure. Issue 17 (2016) - Batyrev, I.G.; Sausa, R.C.
ABSTRACT: We studied TAGzT theoretically using density functional perturbation theory within the plane-wave-pseudo-potential formalism and experimentally by Raman and IR spectroscopy at ambient and high pressure. The modeled spectra predict reasonably well the experimental spectra at ambient pressure and the Raman vibrational modes at pressures up to 25 GPa. We report the effects of pressure on volume, Raman and IR vibrational modes, and charge distribution of TAGzT.